Front Cover: Asymmetric Ene‐Reduction by F420‐Dependent Oxidoreductases B (FDOR‐B) from Mycobacterium smegmatis (ChemBioChem 8/2023). (22nd March 2023) - Kang, Suk Woo; Antoney, James; Lupton, David W.; Speight, Robert; Scott, Colin; Jackson, Colin J.
Abstract : Asymmetric ene‐reductions of FDOR‐Bs against α, β‐unsaturated compounds reveal a novel class of ene‐reductases utilizing the uncommon cofactor F420 . Our study highlights the key role of Flavin/deazaflavin oxidoreductases B (FDOR‐B) enzymes in acquiring stereocomplementarity with the Old Yellow Enzyme (OYE) family, leading to enhanced versatility of biocatalytic syntheses. The wider distribution of FDOR‐Bs across bacterial genera compared to FDOR‐A enzymes suggests a higher potential for identifying potent activity against industrially relevant substrates. More information can be found in the Research Article by S. W. Kang, C. J. Jackson et al.